Surfactant treatment before first breath for respiratory distress syndrome in preterm lambs: comparison of a peptide-containing synthetic lung surfactant with porcine-derived surfactant - van Zyl JM; Smith J (Dove Medical Press, 2013)
Johann M van Zyl,1 Johan Smith2 1Division of Pharmacology, Department of Medicine, Faculty of Medicine and Health Sciences, Stellenbosch University, Tygerberg, South Africa; 2Department of Paediatrics and Child Health, Tygerberg Children's Hospital, Faculty of Medicine and Health Sciences, Stellenbosch University, Tygerberg, South Africa Background: In a recent study utilizing a saline-lavaged adult rabbit model, we described a significant improvement in systemic oxygenation and pulmonary shunt after the instillation of a novel synthetic peptide-containing surfactant, Synsurf. Respiratory distress syndrome in the preterm lamb more closely resembles that of the human infant, as their blood gas, pH values, and lung mechanics deteriorate dramatically from birth despite ventilator support. Moreover, premature lambs have lungs which are mechanically unstable, with the advantage of being able to measure multiple variables over extended periods. Our objective in this study was to investigate if Synsurf leads to improved systemic oxygenation, lung mechanics, and histology in comparison to the commercially available porcine-derived lung surfactant Curosurf® when administered before first breath in a preterm lamb model. Materials and methods: A Cesarean section was performed under general anesthesia on 18 time-dated pregnant Dohne Merino ewes at 129–130 days gestation. The premature lambs were delivered and ventilated with an expiratory tidal volume of 6–8 mL/kg for the first 30 minutes and thereafter at 8–10 mL/kg. In a randomized controlled trial, the two surfactants tested were Synsurf and Curosurf®, both at a dose of 100 mg/kg phospholipids (1,2-dipalmitoyl-L-α-phosphatidylcholine; 90% in Synsurf, 40% in Curosurf®). A control group of animals was treated with normal saline. Measurements of physiological variables, blood gases, and lung mechanics were made before and after surfactant and saline replacement and at 15, 30, 45, 60, 90, 120, 180, 240 and 300 minutes after treatment. The study continued for 5 hours. Results: Surfactant treatment led to a significant improvement in oxygenation within 30 minutes, with the Synsurf group and the Curosurf® group having significantly higher ratios between arterial partial pressure of oxygen/fraction of inspired oxygen (PaO2/FiO2; P = 0.021) compared to that of the control (saline-treated) animals. Dynamic compliance improved in the three groups over time, with no intergroup differences. All of the surfactant-treated animals survived, and one in the saline group died before the study ended. Histology between groups was not different, showing mild–moderate injury patterns. Discussion: Treatment with surfactants before first breath clearly resulted in improved systemic oxygenation within 30 minutes of instillation. Both Synsurf- and Curosurf®-treated animals experienced similar and more sustained improvement in oxygenation and decreased calculated shunt compared to saline-treated animals. Keywords: respiratory distress syndrome, preterm lambs, pulmonary surfactant, gas exchange, oxygenation